The pathology of Chironex fleckeri venom and known biological mechanisms. (June 2020) - Piontek, Melissa; Seymour, Jamie E.; Wong, Yide; Gilstrom, Tyler; Potriquet, Jeremy; Jennings, Ernest; Nimmo, Alan; Miles, John J.
Abstract: The large box jellyfish Chironex fleckeri is found in northern Australian waters. A sting from this cubozoan species can kill within minutes. From clinical and animal studies, symptoms comprise severe pain, welts, scarring, hypotension, vasospasms, cardiac irregularities and cardiac arrest. At present, there is no cure and opioids are used to manage pain. Antivenom is available but controversy exists over its effectiveness. Experimental and combination therapies performed in vitro and in vivo have shown varied efficacy. These inconsistent results are likely a consequence of the different methods used to extract venom. Recent omics analysis has shed light on the systems of C. fleckeri venom action, including new toxin classes that use pore formation, cell membrane collapse and ion channel modulation. This review covers what is known on C. fleckeri pathomechanisms and highlights current gaps in knowledge. A more complete understanding of the mechanisms of C. fleckeri venom-induced pathology may lead to novel treatments and possibly, the discovery of novel cell pathways, novel drug scaffolds and novel drug targets for human disease. Highlights: Comprehensive review on in vitro and in vivo studies of Chironex fleckeri venom. Catalogs the usefulness of existing and experimental therapies. Contrasts methodologies of Chironex fleckeri venom processing for experimental validation. Details data that indicates Chironex fleckeri venom pathology operates through multiple mechanisms of action. Emphasises that venom characteristics are highly underrepresented across marine phylum.